Dynamic Scenario in HTLV-I Infection - Cobiaga, Romina; Reartes, Walter (Journal of Applied Nonlinear Dynamics, 2026)
In this article we present a model that describes the emerging dynamic scenario of infection with the human T-cell lymphotropic virus (HTLV-I). In this model we incorporate the phase of latency in the infection of the CD4+ lymphocytes, the immune response mediated by CD8+ T lymphocytes and the possible appearance of adult T-cell leukemia (ATL). The proposed model is a six-dimensional, non-linear system of ordinary differential equations that describes the dynamic interactions among different cell types. Several types of biological implications are discussed.